Genetika Yahudi dan Islam dalam Sejarah Peradaban Dunia - Arifin, Zainal (Religió: Jurnal Studi Agama-agama, 2011)
To know the origin of the Jews cannot be separated from the historical existence of Abraham because he was an ancestor of the three monotheistic religions (Judaism, Christianity, and Islam). There are two nations that claim to be the descendants of Abraham: The Jews and the Arabs. The Jews passed down through the line of Prophet Ishâq, then down to the Prophet Ya’qûb that holds Israel (servants of God) so that the prophets who were ethnic Jews call themselves as Israelites, descendants of Israel. This article does not only discuss the origin of the historical roots of Jewish groups, but also explain about another issue that is often become the object of intellectual discourse about Jews that could be classified as religion or merely ethnic. Indeed, on the face can be drawn that they are religious communities (Jews as a religion), but many think not. In fact, most of them prefer to call themselves Jews (ethnic) not Judaism. Jewish religion can we categorize as the ethical religion and not a mystical religion. It is caused the Jewish religion always uphold ethics. These ethical principles are formulated in the ten commandments (al-Was}âyâ al-Ashr). in addition, this paper also discusses the displacement of the Jewish people from one place to another